LINGUISTIC-AXILOGICAL FEATURES OF UZBEK TRADITIONAL CHILDREN`S POETRY - Meylikova Farangis Asqar qizi, Assistent (Western European Studies, 2025)
Analyzing the linguistic-axiological features of Uzbek traditional children's poetry helps in understanding how language and values are interconnected. It is crucial to examine the uniqueness of children's poetry, its role in shaping moral, social, and spiritual values, and how values are conveyed to children through language and its meanings. Poetry not only teaches children language, but also helps in shaping their lifestyles and teaching them moral values. This article will explore the linguistic-axiological features of Uzbek traditional children's poetry, its role in promoting moral and social values, and analyze it from a literary and linguistic perspective
Keywords: axiology; social values; children`s poetry